State of the Field: Digital History. - ROMEIN, C. ANNEMIEKE; KEMMAN, MAX; BIRKHOLZ, JULIE M.; BAKER, JAMES; DE GRUIJTER, MICHEL; MEROÑO‐PEÑUELA, ALBERT; RIES, THORSTEN; ROS, RUBEN; SCAGLIOLA, STEFANIA (History, 2020)
Computing and the use of digital sources and resources is an everyday and essential practice in current academic scholarship. The present article gives a concise overview of approaches and methods within digital historical scholarship, focusing on the question 'How have the digital humanities evolved and what has that evolution brought to historical scholarship?' We begin by discussing techniques in which data are generated and machine searchable, such as OCR/HTR, born‐digital archives, computer vision, scholarly editions and linked data. In the second section, we provide examples of how data is made more accessible through quantitative text and network analysis. The third section considers the need for hermeneutics and data‐awareness in digital historical scholarship. The technologies described in this article have had varying degrees of effect on historical scholarship, usually in indirect ways. With this article we aim to take stock of the digital approaches and methods used in historical scholarship in order to provide starting points for scholars seeking to understand the digital turn in the field and how and when to implement such approaches in their work.